Influence of annealing temperatures on the properties of low aspect-ratio TiO2 nanotube layers. (20th September 2016) - Das, Sayantan; Zazpe, Raul; Prikryl, Jan; Knotek, Petr; Krbal, Milos; Sopha, Hanna; Podzemna, Veronika; Macak, Jan M.
Abstract: The present work reports on the effect of thermal annealing on electrical, optical and structural properties of low aspect ratio self-organized TiO2 nanotube layers formed by anodization of Ti. The average inner diameter and length of the nanotubes was 100 nm and 1 μm, respectively. From the whole range of temperatures (300–600 °C), annealing at 400 °C leads to the formation of crystalline TiO2 nanotube layers with anatase structure offering best electrical and photo-electrochemical properties. Conducting atomic force microscopy studies have been explored for the first time to identify the annealing temperature of nanotube TiO2 layers with best electrical properties.